UJI AKTIVITAS ANALGETIK EKSTRAK ETANOL DAUN SEREH WANGI (Cymbopogon nardus(L) Rendle) PADA MENCIT PUTIH (Mus musculus L) JANTAN DENGAN METODE INDUKSI NYERI CARA KIMIA - Triswanto Sentat; Yulistia Budianti; Lukman Nul Hakim (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2018)
Pain is a sensory and emotional experience related to tissue damage. Fragrant lemongrass (Cymbopogon nardus) is widely used in Indonesia as a traditional medicine, especially used as a pain reliever. Therefor the use of these plants must be scientifically tested. The purpose of this test was to determine the ethanol extract of fragrant lemongrass’s leaves which had analgesic potential in male white mice (Mus musculus) and determine the optimal dose potentially provide analgetic activity. This test was an experimental study and conducted on 25 male white mice (Mus musculus) which were grouped randomly into 5 groups, including negative controls, positive control (Ibuprofen), ethanol extract of fragrant lemongrass’s leaves doses I (200 mg / kg), dose II (400 mg / kg), and dose III (800 mg / kg). Pain induction was performed chemically using perintoneal acetic acid after 30 minutes of treatment given. Analgesic power is calculated using the sum number of stretching mice for 1 hour. The results showed that ethanol extract of fragrant lemongrass’s leaves had analgesic activity at dose I (38.70%), dose II (51.84%) and dose III (59.51%). The optimal dose of ethanol extract of fragrant lemongrass’s leaves is at dose II (400 mg / kg) that had 51.84% analgesic effect. Keywords :    Pain, Cymbopogon nardus, analgesic activity test, male white mice, chemical way induction pain